A new non-intrusive condition monitoring system designed to improve reliability of RCDs - Machocki, Krzysztof; Marhoon, Zahrah; Amjad, Shaarawi; Sehsah, Ossama; Dixon, Tom; Mohammad, Jamal Ud-Din (AGH University of Science and Technology Press, 2021)
Managed Pressure Drilling (MPD) is a technology that allows for precise wellbore pressure control, especially in formations with uncertain geomechanics. The Rotating Control Device (RCD) is a crucial part of the MPD equipment but is prone to failure. Therefore, a new condition monitoring system was developed to improve the reliability of RCDs and eliminate their catastrophic failures during MPD jobs. Non-intrusive sensors were selected during the design of this condition monitoring system. Sensors measure: vibrations, acoustic emissions, rotation, pipe movement, temperatures, and contamination level in the coolant fluid. The system can display the measurements in real-time to the operator, giving early warnings to prevent the RCD's catastrophic failures during the job. Additionally, the data is recorded to allow further processing and analysis using ML and AI techniques.
Journal of Geotechnology and Energy
Bibliogr. s. [18].
Keywords: Managed Pressure Drilling; condition monitoring; Rotating Control Device; MPD; RCD